2012
DOI: 10.1136/jclinpath-2012-200665
|View full text |Cite
|
Sign up to set email alerts
|

Going glass to digital: virtual microscopy as a simulation-based revolution in pathology and laboratory science

Abstract: The recent technological advance of digital high resolution imaging has allowed the field of pathology and medical laboratory science to undergo a dramatic transformation with the incorporation of virtual microscopy as a simulation-based educational and diagnostic tool. This transformation has correlated with an overall increase in the use of simulation in medicine in an effort to address dwindling clinical resource availability and patient safety issues currently facing the modern healthcare system. Virtual m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 70 publications
2
14
0
2
Order By: Relevance
“…However, no previous studies have evaluated the accuracy of WSI diagnosis in the routine practice of gynaecological pathology, and neither are there any data about intraobserver or interobserver agreement in the evaluation of routine gynaecological specimens using CLM. The rate of discrepancies observed in our study is within the range of generally observed intraobserver variability in pathology 27 29. Interestingly, the final consensus diagnosis was in agreement with the WSI evaluation in 22.2% of the major discrepancies and in 35.3% of the minor discrepancies.…”
Section: Discussionsupporting
confidence: 84%
“…However, no previous studies have evaluated the accuracy of WSI diagnosis in the routine practice of gynaecological pathology, and neither are there any data about intraobserver or interobserver agreement in the evaluation of routine gynaecological specimens using CLM. The rate of discrepancies observed in our study is within the range of generally observed intraobserver variability in pathology 27 29. Interestingly, the final consensus diagnosis was in agreement with the WSI evaluation in 22.2% of the major discrepancies and in 35.3% of the minor discrepancies.…”
Section: Discussionsupporting
confidence: 84%
“…10 This technology will only widen in scope and practical application as computer processing speeds increase, as demand for virtual case consultation grows and if adoption into board certification examinations occurs. Dermatology trainees use this technology increasingly and may benefit from formal, curriculum-based early exposure, because we anticipate future competency assessment and practice changes.…”
Section: Discussionmentioning
confidence: 99%
“…3 -6 Diagnostic accuracy comparing virtual slides with glass slides has been found to be comparable among medical students, 7 and virtual slide competency examinations have been shown to correlate with future in-training examination performance of surgical pathology residents. 8 Prior studies also have examined diagnostic concordance involving dermatopathologic specimens, beginning with static image 9 and advancing to real-time virtual microscopy, 10,11 but corresponding literature with direct application to dermatopathology instruction for dermatology residents is sparse. A single study compared diagnostic accuracy between virtual and glass slide microscopy among dermatology and pathology resident trainees.…”
Section: Introductionmentioning
confidence: 99%
“…The improvement of learning while practicing specific skills by the use of simulation-based tools such as phlebotomy or resuscitation models is the main purpose in medical education (19). Similar to these simulation-based techniques used in medical education, virtual slides have already taken their place within the learning process in pathology.…”
Section: Discussionmentioning
confidence: 99%